2010
DOI: 10.1016/j.jaci.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Urinary leukotriene E4/exhaled nitric oxide ratio and montelukast response in childhood asthma

Abstract: Background-A subset of children with asthma respond better to leukotriene receptor antagonists (LTRA) than to inhaled corticosteroids (ICS). Information is needed to identify children with these preferential responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…Urine LTE 4 /FeNO ratio has been utilized as a marker for subjects that respond preferentially to LT modifier drugs compared to inhaled corticosteroids in the management of children with asthma [32]. These subjects tended to have less IgE sensitivity, lower eosinophil counts and less responsiveness to inhaled corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urine LTE 4 /FeNO ratio has been utilized as a marker for subjects that respond preferentially to LT modifier drugs compared to inhaled corticosteroids in the management of children with asthma [32]. These subjects tended to have less IgE sensitivity, lower eosinophil counts and less responsiveness to inhaled corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…doi: 10.7243/2054-9873-4-1 as a marker of subjects who respond preferentially to LT modifier therapy [32,41]. We calculated the urine cys-LT/FeNO ratio in our subjects to help characterize the usefulness of this marker in the obese asthma population.…”
Section: Urine Cys-lt/feno Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…The preferential overexpression of LTC 4 synthase in mast cells and eosinophils in aspirin-intolerant asthma [23] explains why leukotriene modifying drugs are so effective in this patient subgroup [24]. In seeking markers for therapeutic efficacy for LTRAs and ICS, exhaled nitric oxide and the ratio of urinary LTE 4 (the major Cyst LT metabolite)/exhaled NO ratio predicts a better response to montelukast compared with inhaled fluticasone propionate therapy in children with mild-to-moderate asthma [25]. Also, because LTRAs are administered orally, patients tend to be more adherent to treatment, explaining why real life effectiveness (as opposed to efficacy) studies have shown little difference in asthma outcome measures when oral montelukast has been compared with an ICS as initial therapy or a long acting beta agonist (LABA) as add-on therapy to ICS [26].…”
Section: Leukotriene Modifiersmentioning
confidence: 99%
“…In a similar group of children with asthma, liquid chromatography coupled with mass spectrometry was used for analysis of urine samples with similar results [101]. The measurement of urinary leukotriene excretion has been investigated in order to find a marker for response to leukotriene antagonists and some promise of the utility has been found in the ratio of urinary leukotriene E 4 /FeNO [102]. In children with exercise-induced asthma, the change of urinary leukotriene E 4 was significantly higher after an exercise test than in healthy children and tended to be higher than in mild asthmatics, thus, leukotriene E 4 might have some association in controlling exercise-induced asthma [103].…”
Section: Biomarkers In Urinementioning
confidence: 99%